Вікові особливості механічної памяті у школярів з нейросенсорною приглухуватістю = Age features of mechanical memory in schoolchildren with sensorineural hearing loss - Mykola Klishch; Stepan Vadzyuk (Kazimierz Wielki University, 2016)
Klishch M. I., Vadziuk S. N. Вікові особливості механічної памяті у школярів з нейросенсорною приглухуватістю = Age features of mechanical memory in schoolchildren with sensorineural hearing loss. Journal of Education, Health and Sport. 2016;6(8):539-553. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60947 http://ojs.ukw.edu.pl/index.php/johs/article/view/3767       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 26.08.2016.     УДК 612.821.3-02:616.28-008.1]-053.5   ВІКОВІ ОСОБЛИВОСТІ МЕХАНІЧНОЇ ПАМЯТІ У ШКОЛЯРІВ З НЕЙРОСЕНСОРНОЮ ПРИГЛУХУВАТІСТЮ   Кліщ М.І., Вадзюк С.Н.   ДВНЗ «Тернопільський державний медичний університет імені І.Я. Горбачевського МОЗ України» (м. Тернопіль)   Резюме. У школярів різних вікових періодів (молодшого - 7-10 років, середнього - 11-14 років і старшого - 15-17 років)  з нейросенсорною приглухуватістю і з нормальним слухом досліджено показники короткочасної механічної пам'яті на цифри, числа, склади і геометричні фігури з використанням пакету «Пам'ять» комп'ютерного діагностичного комплексу "Effecton Studio". Встановлено, що з віком показники як вербальної (цифри, числа, склади) так і невербальної (образи) пам'яті зростають в обох досліджуваних групах, однак у групі школярів з нейросенсорною приглухуватістю усіх вікових періодів показники невербальної пам'яті були достовірно нижчими, а вербальної - достовірно вищими, ніж в учнів з нормальним слухом. Зроблено висновок, що діти зі слуховою деривацією краще, ніж діти із нормальним слухом, запам'ятовують образи і мають гарно розвинуту короткочасну зорову пам'ять на невербальні стимули, що може бути використано при плануванні корекційної роботи. Ключові слова. Нейросенсорна приглухуватість, пам'ять, вікові особливості.     Klishch M.I., Vadziuk S.N. AGE FEATURES OF MECHANICAL MEMORY IN SCHOOLCHILDREN WITH SENSORINEURAL HEARING LOSS I.Horbachevsky Ternopil State Medical University (Ternopil) Summary. We studied indices of short-term mechanical memory for figures, numbers, syllables and geometric figures in schoolchildren of different age periods (elementary school-age - 7-10 years, middle school-age - 11-14 years, senior school-age - 15-17 years) with sensorineural hearing loss and normal hearing. For this purpose we used package "Memory" of computer diagnostic complex "Effecton Studio". It was found out that with age indices of verbal (figures, numbers, syllables) and non-verbal (images) memory increase in both study groups, but in the group of schoolchildren with sensorineural hearing loss of all age periods indices of non-verbal memory were significantly lower, and indices of verbal memory - significantly higher than in schoolchildren with normal hearing. It was concluded that children with hearing derivation remember images better than children with normal hearing and have well-developed short-term visual memory for non-verbal stimuli, which can be used in planning of remedial work. Keywords. Sensorineural hearing loss, memory, age features.